Apathy in untreated early‐stage Parkinson disease: Relationship with other non‐motor symptoms. Issue 14 (5th November 2014) - Dujardin, Kathy; Langlois, Carole; Plomhause, Lucie; Carette, Anne‐Sophie; Delliaux, Marie; Duhamel, Alain; Defebvre, Luc
Abstract Apathy is a frequent and disabling behavioral disorder in patients with Parkinson's disease (PD). Its prevalence in treatment‐naive patients with early‐stage PD has not been extensively investigated. Moreover, whether apathy is related to other non‐motor symptoms in early‐stage PD is unknown. Our objective was to determine the prevalence and features of apathy and associated factors in a group of treatment‐naive patients with early‐stage PD. Ninety‐five treatment‐naive patients with early‐stage PD participated in the study. Apathy, depression, motor symptoms, and overall cognitive efficiency were assessed. The presence of the main non‐motor symptoms was checked during a detailed clinical interview. Group comparisons were carried out to investigate the association with apathy. Eighteen patients (18.95%) were diagnosed as apathetic, and five of the latter had concomitant depression. Apathetic patients had significantly more severe motor symptoms (P < 0.001) and a lower cognitive status (P = 0.032) than non‐apathetic patients. When considering non‐motor symptoms, apathy was significantly associated only with fatigue (P = 0.007) and anhedonia (P = 0.010), both of which were more prevalent in apathetic patients than in non‐apathetic patients. In treatment‐naive patients with early‐stage PD, apathy was significantly associated with more severe motor symptoms and a lower cognitive status. After adjustment for these factors, apathy appeared to be a relatively isolated, independent symptom because the only other associated non‐motor symptoms were fatigue and anhedonia. © 2014 International Parkinson and Movement Disorder Society